Development of a retooled research curriculum framework for the Philippine Science High School - Leo Peter Dacumos (International Journal of Research in STEM Education)
The projected transition of the Philippine Science High School (PSHS) system's research curriculum from a three-year to a condensed two-year program. Furthermore, PSHS plans to adopt the Project-based Learning (PBL) approach in the coming years.  Positioned ahead of these transitions, the study aims to develop a retooled research curriculum framework aimed at integrating conceptual understanding, procedural skills, and project-based learning (PBL) to optimize student learning outcomes and adapt to changes in pedagogical approaches. The retooled curriculum framework was developed using the 4D Model. The insights and perspectives regarding integrating conceptual, procedural, and project-based learning and the overall experiences within the research curriculum of 22 research teachers and 462 research students from across the eight Philippine Science High School – Luzon campuses were gathered. These insights, perspectives, and experiences led to developing the tripartite research teaching and learning model. Ultimately, the tripartite model serves as the foundation for the proposed retooled research curriculum framework of the Philippine Science High School, particularly in terms of crafted learning outcomes. Overall, the validity results showed a very high level indicating the readiness of the curriculum framework to be deployed and used for its projected transition.